Promosi Pariwisata oleh Duta Wisata “Jegeg Bagus Klungkung” Pada Masa New Normal - Luh Ade Syah Sugiarni; Putu Anom; Ida Bagus Ketut Surya (JURNAL MASTER PARIWISATA, 2022)
Jegeg Bagus Klungkung (JBK) is a representative of the young generation in Klungkung Regency as a tourism ambassador with the aim of being an extension of the promotion of tourist destinations in Klungkung Regency. This study aims to describe the roles and constraints faced by JBK in promoting tourist destinations in Klungkung Regency during new normal period, as well as to formulate a strategic role for JBK in maximizing their role as tourism ambassadors. This study uses the promotion mix theory and strategic planning generated from the SWOT analysis. The relevant approach used in this research is a qualitative approach. Data were collected through observation, interview, documentation, and questionnaires. Primary data were obtained through interviews and filling out questionnaires by JBK and tourism stakeholders. Secondary data is obtained through documents, journals and articles. The study found that JBK has done their role as tourism ambassadors through its advertising and public relations on promotion mix. The obstacles experienced consist of external and internal constraints. The strategic role resulting from the SWOT analysis places JBK's position in that JBK should use an intensive strategic role in market penetration and market development, besides being able to diversify the products or services offered. Keywords: JBK, Tourism Promotion, New Normal.